2021
DOI: 10.3389/fdmed.2021.668056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 9.3 μm CO2 and 2.94 μm Er:YAG Laser vs. Bur Preparations on Marginal Adaptation in Enamel and Dentin of Mixed Class V Cavities Restored With Different Restorative Systems

Abstract: This study aimed to compare marginal adaptation in enamel and dentin before and after aging of laser vs. bur-prepared mixed class V cavities restored by different restorative systems. Seventy two caries-free human molars were distributed to nine experimental groups; cavities were prepared using two different lasers: a handpiece -integrated 2.94 μm Er:YAG laser at 4.5 W, 300 mJ, and 0.75 W, 50 mJ with 15 Hz (LiteTouch, Light Instruments, Israel) and a novel CO2 laser at 12.95 W, 19.3 mJ, and 4.1 W, 6.11 mJ with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Energy is converted to heat and results in burning, melting, or vaporizing of the respective area in dentin (Rezaei et al, 2019 ). One study has shown that a laser could develop adhesion and minimize gap formation and microleakage (Otero et al, 2021 ). Thus, the present study aimed to evaluate the microleakage of cavities treated by Er:YAG laser and CO 2 laser irradiation and bromelain and papain 10% enzyme in composite resin restorations and compare the microleakage scores with acid etched cavities in human molar teeth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy is converted to heat and results in burning, melting, or vaporizing of the respective area in dentin (Rezaei et al, 2019 ). One study has shown that a laser could develop adhesion and minimize gap formation and microleakage (Otero et al, 2021 ). Thus, the present study aimed to evaluate the microleakage of cavities treated by Er:YAG laser and CO 2 laser irradiation and bromelain and papain 10% enzyme in composite resin restorations and compare the microleakage scores with acid etched cavities in human molar teeth.…”
Section: Introductionmentioning
confidence: 99%
“…One study has shown that a laser could develop adhesion and minimize gap formation and microleakage (Otero et al, 2021).…”
mentioning
confidence: 99%